β-Aminopropioamidoximes derivatives as potential antitubercular agents against anthropozoonotic infections caused by Mycobacterium tuberculosis and Mycobacterium bovis - Lyudmila Kayukova; Venera Bismilda; Kairat Turgenbayev; Asem Uzakova; Gulnur Baitursynova; Umirzak Jussipbekov; Meruyert Mukanova; Lyailya Chingissova; Gulnur Dyussembayeva; Assiya Borsynbayeva; Azamat Yerlanuly; Ablay Auyezov (Veterinary World)
Background and Aim: Tuberculosis (TB) remains a significant global health challenge, with increasing incidences of drug-sensitive (DS) and multidrug-resistant (MDR) TB. In addition, Mycobacterium bovis-induced zoonotic TB (zTB) presents treatment difficulties due to its resistance to pyrazinamide and the prolonged treatment duration required. This study aims to evaluate the antitubercular potential of β-aminopropioamidoxime derivatives against DS and MDR Mycobacterium tuberculosis and M. bovis strains, and utilizing the SwissADME prognostic tool to predict the drug- and lead-likeness of the described compounds.